Improving Reading Fluency Of Fourth-Grade Elementary Students Through Structured Reading Materials - Desi Afrianti; Apri Pendri; Meksi Rahma Nesti (Jurnal Hata Poda, 2025)
This study aims to describe the improvement of elementary school students’ reading fluency through the use of structured reading materials. The study employed a qualitative approach with a case study design conducted at the Grase Tutoring Center. The research subjects consisted of five fourth-grade elementary school students who experienced difficulties in reading fluency. Data were collected through observation, oral reading tests, interviews, and documentation. Data were analyzed qualitatively through data reduction, data display, and conclusion drawing.The results indicate that the implementation of structured reading materials effectively improved students’ reading fluency. Improvements were observed in reading accuracy, reading speed, smoothness without unnecessary pauses, and reading intonation. The average reading fluency score increased from 58.4 in the pre-test to 78.4 in the post-test. In addition, students demonstrated increased self-confidence and higher engagement during the reading instruction process. These findings suggest that structured reading materials can serve as an effective alternative instructional strategy to enhance the reading fluency of elementary school students, particularly those who still experience reading difficulties.